Impacts of a workplace physical activity intervention on employee physical activity & mental health for NHS staff in Wales: an evaluation of the pilot Time to Move initiative - Ford, Kat; Hughes, Karen; Bellis, Mark A; Sharp, Catherine (International Journal of Population Data Science, 2022)
Background Estimates show that only half of adults in Wales meet the UK recommend guidelines for physical activity. In 2015, the financial burden of physical inactivity to the Welsh NHS was estimated to be £35 million. Workplace interventions promoting physical activity can result in positive outcomes for employee health, wellbeing, productivity, job satisfaction and reduced absenteeism. However, the majority of such interventions are prescriptive in the type/duration of physical activity to be completed. In response to Welsh public opinion that employers should do more to help improve the health of their workforce, Public Health Wales (PHW) developed the Time to Move initiative - a 12-month pilot providing employees the opportunity to use one hour (pro rata) of paid work time per week for physical activity of their choice. Methods The Time to Move initiative was evaluated using a pre-experimental time series design. Data were collected using online questionnaires at baseline (June-August 2018), mid-initiative (Dec 2018) and 12-months post-initiative (June–Aug 2019). All measures were self-reported and included physical activity (MET-minutes/week), general health (0, poor – 100, good) and mental well-being (SWEMWBS), job satisfaction (1, very dissatisfied – 5, very satisfied) and participant demographics (e.g. age, gender, pay band). Findings 625 participants completed measures at 12-months post-initiative (72.8% of baseline sample), representing just over a third of all PHW employees. Of those completing all relevant measures, 57.7% reported increased physical activity levels at 12-months compared to baseline (30.6% decreased; 11.6% no change). 75.3% of the sample met UK physical activity guidelines at 12-months compared to 58.8% at baseline. Individuals with the lowest reported levels of physical activity at baseline (n=223) made the greatest improvements - increasing their weekly moderate physical activity by >2.5 hours. Those with moderate activity (n=269) increased by 58 minutes/week and those with high activity levels (n=50) decreased by >4 hours/week. Overall, a small but statistically significant improvement was seen in mental well-being over the study period (mean scores, 22.4 baseline, 23.2 12-months), with participants with categorised as having low mental well-being at baseline benefitting the most. For self-reported health, 34.7% increased their rating (change of at least 10 points), 54.6% had no change and 10.7% declined. The proportion very/quite satisfied with their job increased from 64.4% to 72.0%, with 33.4% of individuals reporting increased job satisfaction (19.6% decreased). Conclusions The Time to Move initiative demonstrates how organisations can encourage and enable their employees to improve their health. Evaluation findings indicate that the provision of paid time to engage in physical activity resulted in positive outcomes for many employees. However, understanding of the impact of the intervention over a longer-period of time is required, including how continued participation may have been impacted by COVID-19-related restrictions.